The Role of Community-Based Educational Initiatives in Sustaining Education During the Israeli Aggression on Gaza: A Parental Perspective - Adwan, Nael Hassan; Shuaib, Subhi Rabee (Journal of Educational and Psychological Sciences, 2025)
This study aimed to analyze the role of community-based educational initiatives in promoting the continuity of education during the Israeli aggression on the Gaza Strip in 2023, from the perspective of parents. The research responds to an urgent need to understand the roles local communities can play in supporting education amid the collapse of the formal education system due to war, during which schools were shut down, hundreds of thousands of students were displaced, and families faced complex educational and psychological challenges.The study adopted a descriptive-analytical methodology and employed an electronic questionnaire distributed to a sample of 276 parents, in addition to a qualitative analysis of open-ended responses. The questionnaire covered four main areas: participation in initiatives, their effectiveness, challenges faced, and overall evaluation. The findings indicate that community-based initiatives played an effective role in mitigating learning loss and providing psychosocial support for students, despite significant challenges on the ground. Results also revealed a statistically significant correlation between parents’ participation and their satisfaction with these initiatives, while no statistically significant differences were found based on demographic variables. Open-ended responses reflected a strong awareness of the importance of such initiatives, alongside identified gaps in coverage and coordination. The study recommends adopting national emergency education policies that recognize and support community initiatives through institutional planning and funding, and empowering families as educational actors during crises.